Disparitas Isbat Nikah: Kasus Isteri Terikat Perkawinan Sebelumnya di Pengadilan Agama Gorontalo - Amiruddin, Shalsa; Insani , Nur; Lahaling, Hijrah (Jurnal Litigasi Amsir, 2024)
This study analyzes the judge’s considerations in the case of isbat nikah of wives who are still bound by previous marriages, focusing on case study Number 311/Pdt.P/2019/PA. Gtlo and Number 255/Pdt.P/2022/PA. Gtlo at the Gorontalo Religious Court. The method used is juridical normative legal research. The results show that the judge in the first case granted the isbat nikah application, providing clarity and legality of the marital status that was previously unclear, based on the principles of justice, certainty, and utility. On the contrary, the second case rejected the application, resulting in uncertainty of the legal status for the applicant and their children. This disparity in decisions is caused by factors such as legal structure, legal substance, and legal culture